Potential solutions to financing problems among the poor: case of Baitul Maal Wa Tamwil in Indonesia - Siraj, Mukhtar Arif; Riyadi, Aditya Hadid; Sheik Abdukad, Abdukadir Abdullahi; Jama, Abdihakim; Redzuan, Nur Harena (IIUM Institute of Islamic Banking and Finance, 2021)
Currently, many people, especially those in the poor category, do not have access to most of the financial services, especially from banking institutions. For example, in Indonesia, currently, there are approximately 91.3 million Indonesians who are still untouched by financial or banking services (Bank Indonesia, 2020). In view of the difficulties in accessing financing to undertake their economic activities, the poor have been economically unproductive and remained in the cycle of poverty. In this regard, there is a need for non-bank financial institutions to play a role in reaching people who are still unbanked. There are several models of non-bank financial institutions that can be used to solve this problem. Indonesia as a country with the largest Muslim population in the world has a very well-known non-bank Islamic financial institution, namely Baitul Maal wa Tamwil (BMT). With a business model that focuses on the lower-middle-class economy and the MSME sector, it is hoped that BMT will be able to solve the problem of access to financial services for the poor. This study aims to determine the issues and challenges of BMT in providing financial service solutions to the poor in Indonesia. In addition, this study provides alternative solutions to the problems faced by BMT in their efforts to improve financial inclusion in Indonesia. In methodology, the study uses qualitative methods based on literature reviews from journals, research, and secondary data. It is hoped that this study would provide enriching inputs in the development of the Islamic microfinance industry in Indonesia as well as in other countries.